"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppression; thématiques; éducation sexuelle

La grande arnaque : sexualité des femmes et échange économico-sexuel - Tabet, Paola (Bibliothèque du féminisme, 2004)
Dans la majorité des sociétés connues, la sexualité apparaît comme un échange asymétrique et non réciproque entre hommes et femmes, une compensation masculine pour une prestation féminine, un paiement qui peut revêtir les formes les plus variées en échange d'une sexualité transformée en service. Comment se fait-il que les hommes, même plongés dans les situations les plus misérables, peuvent se payer le service sexuel d'une femme - alors que non seulement les femmes n'ont pas, sauf exception, cette possibilité mais de plus n' ont même pas droit à leur propre sexualité ?
Keywords: EDI; approches et analyses; cycles supérieurs; discipline; division sexuelle du travail; ethnologie; fem1000; inégalités; premier cycle; rapports sociaux de sexe; sciences; sciences humaines; sexualité; systèmes d'oppression; thématiques; théories féministes; épistémologie

Fantasies of femininity: Reframing the boundaries of sex - Ussher, Jane M. (Rutgers University Press, 1997)
In Fantasies of Femininity, Jane Ussher focuses on unraveling the contradictory visions of feminine sexuality: the fact that representations of the definition of woman seethe with sexuality yet for centuries women have been condemned for exploring their own sexual desires. In her quest for the sources of feminine representation, Ussher interviewed dozens of women - as well as some men - and combed popular media - from Seventeen to Cosmopolitan and Dallas to Donahue - to identify what shapes women's symbolic images of sex and femininity. Ussher argues that women have effectively resisted and subverted these archetypal fantasies of femininity, and in the process of so doing, reframed the very boundaries of sex. In this way, she exposes as myth much of what we think we know about "woman" and about "sex."
Keywords: approches et analyses; discipline; fem1000; inégalités; premier cycle; psychologie; sciences humaines; sexualité; sexualité féminine; stéréotypes; systèmes d'oppression; thématiques; études culturelles